DETERMINATION OF CETIRIZINE IN HUMAN PLASMA AND ITS VALIDATION OF METHOD USING HPLC TECHNIQUE: Cetrizine determination in human plasma using HPLC technique - Binti Zuhri, Siti Hazar; Azad, A.K.; Mia, Abdur Rashid; Uddin, ABM Helal; Mohd. Nawi, Mohamed Sufian Bin (Journal of Drug Delivery and Therapeutics, 2019)
This reseach project is dedicated to analyze cetirizine in human plasma by using HPLC qualitatively and quantitatively, to make a reliable bioanalysis of this drug in human plasma with a goal to utilise it in pharmacokinetics studies. In this research project, cetirizine was extracted from plasma using liquid-liquid extraction by dichloromethane and ethyl acetate. The results in terms of accuracy and precision are compared. For both of the methods, amlodipine was used as the internal standard. Separation was carried out by Phenomenex C18 chromatography column. The mobile phase used here is 35:65, v/v of Acetonitrile to 0.3% triethylamine (TEA) buffer fixed at pH 3 by phosphoric acid, with flow rate of 1mL/min. The column temperature was set at 30 ᵒC. Various wavelength detector (VWD) was used, and detection was set at 237nm. The analysis was linear from 30ng/mL to 500ng/mL. Overall the recovery is more than 90% when using dichloromethane and more than 65% when using ethyl acetate. Keywords: Bioanalysis, Method validation, Cetirizine, Human plasma, HPLC